Strategic IT governance and performance frameworks in large organizations - Maleh, Yassine 1987-; Sahid, Abdelkebir 1983- (IGI Global, 2019)
"This book discusses the strategic information technology governance in large organizations. It also explores the strategic IT governance through new approaches: IT governance maturity in large organizations, IT agility, and information system security"--